Factors Influencing Implementation of Family-Centered Care in a Neonatal Intensive Care Unit - Oude Maatman, Sabine M.; Bohlin, Kajsa; Lilliesköld, Siri; Garberg, Håvard T.; Uitewaal-Poslawky, Irina; Kars, Marijke C.; van den Hoogen, Agnes (Frontiers in Pediatrics, 2020)
Background: Approximately 10% of all births worldwide are preterm. Often these infants are admitted at a Neonatal Intensive Care Unit (NICU). The NICU environment with periods of unnatural light, noise and repeated disturbances is very stressful for infants admitted to the NICU. In addition separation of parents causes stress for both infant and parents. A way to support and include parents in the care for their infants is Family-Centered Care (FCC). FCC is an approach of planning, delivery and evaluation of healthcare, based on a partnership between healthcare professionals and families of patients. Parents of infants who were admitted to an FCC unit were less stressed compared to parents at a Standard Care unit. Aim: Although FCC is beneficial to families and patients, implementation can be challenging. Therefore it is important to know which factors can contribute or withhold the implementation of FCC. This study explored factors that influence implementation of FCC in NICU’s according to healthcare professionals that work in a NICU with the concept FCC. Method: A descriptive generic qualitative design with semi-structured interviews and inductive thematic analyses was used. This international multi-center study was conducted in three hospitals in three European countries: Sweden, Norway and The Netherlands. Results: Seven neonatal care nurses, one nurse assistant, five neonatologists and three managers participated in this study. Four aspects were identified, when analyzing the data, namely: Behavioral change in staff, Family needs, Environment and Communication. Most important is that almost all healthcare professionals described that the mind-set of the professional influences the implementation of FCC. Conclusion: The mind-set of healthcare professionals in seeing parents as primary caregiver influences the way FCC is practiced and how parents are involved in the care for their infant.